A review of conservative management of camptodactyly in children and adolescents. (December 2014) - Lethbridge, Katrina; Wollin, Leslie
Introduction: The purpose of this review was to systematically evaluate the best available evidence for the conservative management of children and adolescents diagnosed with camptodactyly and propose recommendations to guide clinical practice. Methods: A search of six electronic databases and manual searches were carried out in January 2014. The search strategy aimed to identify any published clinical practice guidelines as well as articles on the conservative management of camptodactyly for children and adolescents. Included articles were appraised using the McMaster Critical Review Forms for quantitative studies and assigned a level of evidence according to the National Health and Medical Research Council guidelines. Results: No published clinical practice guidelines were located; however, five quantitative articles met the inclusion criteria from the 31 articles identified. The evidence from all included studies was classified according to the National Health and Medical Research Council guidelines as level IV, pre–post study design. All were retrospective. Included studies demonstrate clinically significant changes in passive joint range of motion following conservative treatment protocols. The results of the literature review, combined with clinical experience, were used to develop recommendations to guide clinical practice in the conservative management of children and adolescents with camptodactyly. Discussion: The effectiveness of conservative therapy for camptodactyly is promising but evidence remains weak. More rigorous research is needed and the proposed recommendations could be used to inform future research for the conservative treatment of camptodactyly in children and adolescents.